A Regression Analysis of the Effect of Syntactic Competence on Arabic Text Reading Speed - Mahfudloh, Putri Syarifatul; Basith, Abdul (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study examines the influence of syntactic competence on Arabic reading speed. Using a quantitative approach with 30 students as the sample, syntactic competence was measured with objective tests, while reading speed was directly recorded from authentic texts. Using a quantitative, correlational, ex post facto design, data were collected from the student population at Darussalam Al-Arofah Dormitory in Banyuwangi. A sample of 30 students was selected using saturation sampling techniques. The data sources were objective test scores for syntactic competence (20 multiple-choice questions) and reading speed scores (Words Per Minute/WPM) measured using authentic Arabic texts containing 80 words. The data analysis techniques used were descriptive statistics, assumption tests (Shapiro-Wilk normality and linearity), Pearson's Product-Moment correlation, and simple linear regression. The analysis revealed a strong, significant positive relationship between the two variables (r = 0.637). Every increase in syntactic score contributes to an improvement in reading speed. The obtained regression model (Ŷ = 23.45 + 0.62X) explains 40.6% of the variation in speed, confirming that a solid grasp of grammar is an important pillar for efficient reading. This finding supports language processing theory and provides practical guidance for educators: integrating syntactic reinforcement with reading fluency exercises is a key strategy for effective Arabic literacy development in the digital world.